Taxation in Uzbekistan’s Companies-Accounting Practices, Compliance, and Strategic Implications (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This research contends that the evolving tax regime in Uzbekistan has fundamentally reshaped the accounting practices, compliance strategies, and financial reporting of companies operating within the country. The complexity and dynamism of Uzbekistan’s tax laws-including recent reforms in corporate income tax (CIT) rates, turnover taxes, and the introduction of risk-based tax audit mechanisms-demand that companies implement robust, adaptive accounting systems and proactive tax planning. Empirical evidence and professional practice reveal that companies able to align their accounting policies with the nuances of Uzbek tax legislation not only ensure compliance and minimize fiscal risk but also gain a competitive advantage through optimized tax burdens and enhanced financial transparency. The study further argues that the convergence of tax accounting and financial reporting, supported by digitalization and professional advisory services, is crucial for sustainable business growth and for meeting the increasing expectations of regulators and stakeholders in Uzbekistan’s rapidly developing economy.